INSTALLATION OF MORAL VALUES IN STUDENTS AT SD NEGERI 013848 GEDANGAN - Fachrunisanurika; Ulayyaelvira (International Journal of Students Education, 2023)
In the context of what the teacher is able to do is moral reasoning. The purpose of this study is to reveal and know the moral standards of employees of SD Negeri 013848 Gedangan. The keywords used in this research methodology are qualitative, with a descriptive research methodology. Data collection was carried out using interview and observation technology. All data was then processed using qualitative data analysis techniques, data editor, data model (data presentation), verification of conclusions, and perceptual analysis. The findings of this researcher can be stated as follows in the results of data analysis. First, the teacher introduces ten moral principles to students. Third, the relationship between students and their teachers is strong and useful for instilling religious knowledge. Apart from going to school in elementary school, students can also study at home such as opening tutoring. The focus of this study is that the moral guidance given to employees at SD Negeri 013848 Gedangan is the most common indicator that everything is going well, although there are some teachers who may not fully understand the moral guidance that must be given. Through using the school grounds and working with other students, they recite the moral principles that apply to each subject studied. They also advise students on a daily basis. In contrast to that, students of SD Negeri 013848 Gedangan have good moral behavior because they have learned some moral truths and make it easier for their teachers to practice them. The focus of this study is that the moral guidance given to employees at SD Negeri 013848 Gedangan is the most common indicator that everything is going well, although there are some teachers who may not fully understand the moral guidance that must be given. Through using the school grounds and working with other students, they recite the moral principles that apply to each subject studied. They also advise students on a daily basis. In contrast to that, students of SD Negeri 013848 Gedangan have good moral behavior because they have learned some moral truths and make it easier for their teachers to practice them. The focus of this study is that the moral guidance given to employees at SD Negeri 013848 Gedangan is the most common indicator that everything is going well, although there are some teachers who may not fully understand the moral guidance that must be given. Through using the school grounds and working with other students, they recite the moral principles that apply to each subject studied. They also advise students on a daily basis. In contrast to that, students of SD Negeri 013848 Gedangan have good moral behavior because they have learned some moral truths and make it easier for their teachers to practice them. although there are some teachers who may not fully understand the moral guidance that must be given. Through using the school grounds and working with other students, they recite the moral principles that apply to each subject studied. They also advise students on a daily basis. In contrast to that, students of SD Negeri 013848 Gedangan have good moral behavior because they have learned some moral truths and make it easier for their teachers to practice them. although there are some teachers who may not fully understand the moral guidance that must be given. Through using the school grounds and working with other students, they recite the moral principles that apply to each subject studied. They also advise students on a daily basis. In contrast to that, students of SD Negeri 013848 Gedangan have good moral behavior because they have learned some moral truths and make it easier for their teachers to practice them.